Comparison of variation of renal functions after ESWL and Pyelolithotomy for Kidney Stone - Mudassar Saeed Pansota, Muhammad Ajmal Malik, Hafiz Muhammad Tariq, Muhammad Shahzad Saleem, Mumtaz Rasool (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The effect of ESWL and pyelolithotomy shows that parameters as serum creatinine, renal plasma flow, GFR, and estimated GFR are disturbed for different duration. Moreover, the time required for assessment can be significant because the acute functional deterioration of kidney may resolve and it is hard to measure the chronic injury. Objectives: To frequency of patients of renal stone that fall in the ESWL range and pyelolithotomy range and also to compare the percentage change in GFR in patients undergoing ESWL versus pyelolithotomy. Materials & Methods: A total of 126 patients with diagnosed as having renal stone on USG KUB, 15 to 65 years of age were included. Patients having nephrolithotomy, post procedural ureteric obstruction and UTI were excluded. Patients falling in ESWL range and pyelolithotomy range were recorded. Patients were called for follow up 3 months after surgery. GFR was measured and percentage change was calculated. Results: In this study, ESWL was done in 39 (30.95%) patients and pyelolithotomy in 87 (69.05%) patients. Mean baseline GFR in ESWL group was 32.49 ± 5.98 and in pyelolithotomy group was 31.17 ± 4.621. Mean GFR after 3 months in ESWL group was 45.13 ± 7.54 and in pyelolithotomy group was 44.25 ± 5.96. Mean percentage change in GFR in ESWL group was 36.82 ± 21.27 and in pyelolithotomy group was 44.05 ± 22.40 with p-value of 0.087. Conclusion: This study concluded that frequency of patients of renal stone that fall in the pyelolithotomy range is higher as compared to ESWL range and also the percentage change in GFR in patients undergoing pyelolithotomy is higher as compared to ESWL.